2015
DOI: 10.1002/adfm.201501058
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Cuprate Crystal Growth: The Role of Mixed Metal Carbonates

Abstract: The mechanism of formation of the superconductor Bi2Sr2CaCu2O8+x (Bi‐2212) has been an open question since its discovery in 1988. By controlling crystal growth through the use of biopolymers as multivalent cation chelating agents, it is demonstrated through X‐ray diffraction and thermogravimetric analysis, that it is the formation of a mixed metal carbonate eutectic that promotes the formation of the target phase. X‐ray diffraction experiments, supported by infrared spectroscopy, identify this phase as (Sr1−x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…3.3.1. Via Rietveld Refinement of 5:1 Ammonium Nitrate/YBaCu Nitrates Previous studies have shown that during the calcination, in every case, metal carbonates were formed and those crystal compositions were identified as promoters of high yields of single crystal phases [25]. The metal carbonates are formed via the interaction of the metal cation with a carboxylic coordinating sphere [12]; therefore, with the use of compounds such as ammonium nitrate, YBaCu nitrates, and no carbon source added to the reaction, the formation of such crystals should not be expected.…”
Section: Temperature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3.3.1. Via Rietveld Refinement of 5:1 Ammonium Nitrate/YBaCu Nitrates Previous studies have shown that during the calcination, in every case, metal carbonates were formed and those crystal compositions were identified as promoters of high yields of single crystal phases [25]. The metal carbonates are formed via the interaction of the metal cation with a carboxylic coordinating sphere [12]; therefore, with the use of compounds such as ammonium nitrate, YBaCu nitrates, and no carbon source added to the reaction, the formation of such crystals should not be expected.…”
Section: Temperature Analysismentioning
confidence: 99%
“…Based on this result, the formation of metal carbonates is essential due to the fact that those crystalline compositions thrive even under non-carbon conditions, as elements like barium can react with carbon that the atmosphere provides. Therefore, adding chemical compounds that supply carbon to the reaction media provides faster thermal synthetic routes and higher purity [12,25]. Based on this result, the formation of metal carbonates is essential due to the fact that those crystalline compositions thrive even under non-carbon conditions, as elements like barium can react with carbon that the atmosphere provides.…”
Section: Temperature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our method also allows for precise control of mass transfer and can serve as a good model system to investigate crystal growth. Combining the micromodel with in situ spectroscopic imaging techniques, such as Raman or fluorescence, one can monitor the changes in polymorphs and morphologies which will reveal mechanisms of coprecipitation processes . Advanced in situ spectroscopic techniques can also be used to visualize adsorption or desorption of chemical species on the carbonate rocks.…”
Section: Resultsmentioning
confidence: 99%
“…Additional solution-state methods of inorganic material synthesis include biomimetic syntheses, which have been applied to the synthesis of cuprate superconductors with great success. [13][14][15] These methods utilise a natural biopolymer, such as dextran or sodium alginate, to chelate stoichiometric amounts of metal salts in solution. In these cases, the oxygen atoms in the biopolymer can chelate to the metal ions, forming a so-called egg-box conformation, which enables the biopolymer to behave similarly to the polymeric gel in the Pechini method.…”
Section: Introductionmentioning
confidence: 99%